A Supervisory Load-Leveling Approach to Improve the Voltage Profile in Distribution Network - Mokhtari, G.; Nourbakhsh, G.; Ledwich, G.; Ghosh, Arindam (The Institute of Electrical and Electronic Engineers (IEEE), 2015)
This paper suggests a supervisory control for storage units to provide load leveling in distribution networks. This approach coordinates storage units to charge during high generation and discharge during peak load times, while utilized to improve the network voltage profile indirectly. The aim of this control strategy is to establish power sharing on a pro rata basis for storage units. As a case study, a practical distribution network with 30 buses is simulated and the results are provided.